Differences in Tri-Trophic Community Responses to Temperature-Dependent Vital Rates, Thermal Niche Mismatches and Temperature-Size Rule - Dijoux, Samuel; Smalås, Aslak; Primicerio, Raul; Boukal, David S (Ecology letters, 2024)
Warming climate impacts aquatic ectotherms by changes in individual vital rates and declines in body size, a phenomenon known as the temperature-size rule (TSR), and indirectly through altered species interactions and environmental feedbacks. The relative importance of these effects in shaping community responses to environmental change is incompletely understood. We employ a tri-trophic food chain model with size- and temperature-dependent vital rates and species interaction strengths to explore the role of direct kinetic effects of temperature and TSR on community structure along resource productivity and temperature gradients. We find that community structure, including the propensity for sudden collapse along resource productivity and temperature gradients, is primarily driven by the direct kinetic effects of temperature on vital rates and thermal mismatches between the consumer and predator species, overshadowing the TSR-mediated effects. Overall, our study enhances the understanding of the complex interplay between temperature, species traits and community dynamics in aquatic ecosystems.
Keywords: Body Size; thermal niche mismatch; Climate Change; ekosystém; metabolic ecology; emergent Allee effect; velikost těla; trophic chain; klimatické změny; potravní řetězec; Models, Biological; zvířata; Temperature; Food Chain; biologické modely; alternative stable states; Ecosystem; temperature‐size rule; warming; teplota; Animals